Perlindungan Konsumen Terkait Tenggang Waktu Pemberian Ganti Rugi Terhadap Barang Garansi. - Cristina, Desy; Sasmiar, Sasmiar (Zaaken: Journal of Civil and Business Law, 2025)
The grace period for compensation for damage to goods under warranty is an important aspect of consumer protection. This study aims to 1) identify and analyze consumer protection regulations related to the time limit for compensation for damage to goods under warranty based on the principle of legal certainty (ius constitutum), and 2) identify and analyze the time limit for compensation for damage to goods under warranty for future law (ius constituendum). The method used in this study is the normative legal method. The results of the study indicate that consumer protection in the Indonesian legal system currently faces challenges, particularly regarding the provision of warranty guarantees for purchased products. The main problem lies in the unclear time limit for settling compensation claims during the warranty period and the conflict of norms in Law No. 8 of 1999 concerning Consumer Protection, namely between Article 19 paragraph (3) and Article 27 letter e. This ambiguity weakens the position of consumers and opens opportunities for business actors to avoid legal responsibility. Therefore, legal reform (ius constituendum) is needed to establish that compensation claims must be processed after the consumer files a claim, not within 7 days of the transaction. Technology-based oversight and the involvement of institutions such as the National Consumer Protection Agency (BPKN) are also crucial to ensure business compliance. This reform aims to create stronger legal protection, promote fairness, legal certainty, and enhance the professionalism of businesses within a sustainable consumer protection system.